Impact of Super-diversity on the Use of Nepali Language - Tembe, Harkaraj (Rupantaran: A Multidisciplinary Journal, 2025)
This paper deals with the influence of diverse cultures and languages in the use of Nepali language in the context of Dhankuta. The aim of this paper is to examine the impact of super-diversity on the use of the Nepali language and to identify potential factors contributing to linguistic super-diversity. This paper could be a reference for those interested in learning more about linguistic super-diversity. The study was conducted with college students in Dhankuta bazaar. It was primarily guided by a qualitative research design to examine the students' utterances. The results show that many participants from various linguistic backgrounds reproduced Nepali in a somewhat distinctive ways which contribute to the development of new language varieties. Linguistic super-diversity mainly stems from factors like migration, political changes, globalization, religion, education, technology, culture, economics, multilingual societies, and inter-caste marriages. Understanding the impact of super-diversity on language use is crucial for all involved in language education to promote successful language teaching and learning.